"Empowering Our People": Impact of a Culturally Adapted Evidence-Based Intervention on Sexually Transmitted Infection Risks Among Native Americans With Binge Substance Use. Issue 9 (September 2021) - Tingey, Lauren; Chambers, Rachel; Littlepage, Shea; Lee, Angelita; Slimp, Anna; Melgar, Laura; Cwik, Mary; Gaydos, Charlotte; Rompalo, Anne; Rosenstock, Summer
Abstract : Background: The objective of this study was to evaluate a culturally adapted evidence-based intervention called EMPWR (Educate, Motivate, Protect, Wellness and Respect) for impacts on sexually transmitted infection (STI) screening and sexual health risk behaviors. Methods: We enrolled Native American adults with recent binge substance use from a rural, reservation community in the Southwest into a 1:1 randomized controlled trial conducted on July 2015 to June 2019. All participants were offered non–clinic-based self-administered STI screening. Data were collected via self-report at baseline, 3 months, and 6 months after the intervention. Baseline and end line data are presented. Results: Three hundred one participants were enrolled and had a mean age of 33.8 years; 46.5% of the sample were female, and 9.1% were employed at baseline. EMPWR participants were more likely to complete STI self-screening than control participants (38.2% vs. 23.8%, P = 0.0275). EMPWR participants reported fewer unprotected sex acts in the past 3 months (9.3 vs. 16.0, P = 0.001) and were more likely to refuse sex if their partner was not tested (23.6% vs. 12.4%, P = 0.049). The between-group difference in STI positivity 1 year after study completion was nearing statistical significance (intervention: 39.5% vs. control: 59.6%, P = 0.0575). Conclusions: The culturally adapted evidence-based intervention, EMPWR, increased uptake of STI screening and refusal of sex if partner was not STI tested and decreased the frequency of unprotected sex acts among Native American adults with recent binge substance use living on a rural reservation. Future research is needed to examine EMPWR impacts among other Native American subgroups and its potential for advancing sexual health equity in this high-priority population. Abstract : Impact evaluation of a culturally adapted evidence-based intervention demonstrated increases in sexually transmitted infection screening, refusal of sex if partner not tested, and reductions in unprotected sex among Native American adults with binge substance use.Supplemental digital content is available in the text.